PENGARUH PERSEPSI MASYARAKAT TENTANG WAKAF UANG TERHADAP MINAT BERWAKAF UANG DI MASJID JAMI’BAITU NUR DESA BERINGIN SANGGUL KABUPATEN MERANGIN - Holil Kibron; Sucipto Sucipto; M.Taufik Ridho (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study discusses the influence of public perceptions of cash waqf on interest in cash woaf at the Jami'baitu Nur Mosque, Beringin Sanggul Village, Merangin Regency. The research is a quantitative research, collecting data using questionnaires. The sample in this study was the community of Beringin Sanggul Village, Merangin Regency. totaling 90 people. The research data obtained r Square of 0.873 and the I test showed that people's perceptions of cash waqf (X) had a significant effect on interest in cash wauf, this was indicated by the tcount of public perceptions of cash waqf of 8.713, with a table of 1.662, the perception variable the community regarding cash waqf has a significant effect on interest in cash waqf. In other words, between variable V and variable Y there is a significant influence. The results of this study suggest that those who have a deeper understanding of cash waqf always provide more understanding and attention to the community, so that more and more people are interested in carrying out cash waqf.